Impact of Pneumococcal Conjugate Vaccine on Pediatric Tympanostomy Tube Insertion in Partial Immunized Population. (9th March 2015) - Wang, Mao-Che; Wang, Ying-Piao; Chu, Chia-Huei; Tu, Tzong-Yang; Shiao, An-Suey; Chou, Pesus
Abstract : Objective . To investigate the impact of seven-valent pneumococcal conjugate vaccine on tube insertions in a partial immunized pediatric population. Study Design . Retrospective ecological study. Methods . This study used Taiwan National Health Insurance Research Database for the period 2000–2009. Every child under 17 years old who received tubes during this 10-year period was identified and analyzed. The tube insertion rates in different age groups and the risk to receive tubes in different birth cohorts before and after the release of the vaccine in 2005 were compared. Results . The tube insertion rates for children under 17 years of age ranged from 21.6 to 31.9 for 100, 000 persons/year. The tube insertion rate of children under 2 years old decreased significantly after 2005 in period effect analysis ( β = −0.074, P < 0.05, and the negative β value means a downward trend) and increased in children 2 to 9 years old throughout the study period (positive β values which mean upward trends, P < 0.05). The rate of tube insertion was lower in 2004-2005 and 2006-2007 birth cohorts than that of 2002-2003 birth cohort (RR = 0.90 and 0.21, 95% CI 0.83–0.97 and 0.19–0.23, resp.). Conclusion . The seven-valent pneumococcal conjugate vaccine may reduce the risk of tube insertion for children of later birth cohorts. The vaccine may have the protective effect on tube insertions in a partial immunized pediatric population.